2016
DOI: 10.1097/bot.0000000000000631
|View full text |Cite
|
Sign up to set email alerts
|

Suprapatellar Intramedullary Nail Technique Lowers Rate of Malalignment of Distal Tibia Fractures

Abstract: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 20 publications
4
87
4
Order By: Relevance
“…The rate of malalignment in the SP group (4.8%, 2/42) was signi cantly lower than that in the IP group (14.3%, 8/56). Our results are consistent with the result of a previous study reporting the radiographical outcomes following the treatment of distal tibia fractures using the SP and IP approaches [24]. Frank R compared the radiographical outcomes following the treatment with IMN using the SP and IP approaches and reported that there was a 26.1% incidence of angular deformity greater than 5 degrees when IMN insertion was performed using the IP approach.…”
Section: Discussionsupporting
confidence: 91%
“…The rate of malalignment in the SP group (4.8%, 2/42) was signi cantly lower than that in the IP group (14.3%, 8/56). Our results are consistent with the result of a previous study reporting the radiographical outcomes following the treatment of distal tibia fractures using the SP and IP approaches [24]. Frank R compared the radiographical outcomes following the treatment with IMN using the SP and IP approaches and reported that there was a 26.1% incidence of angular deformity greater than 5 degrees when IMN insertion was performed using the IP approach.…”
Section: Discussionsupporting
confidence: 91%
“…Although originally described for proximal tibial nailing, semi-extended positioning of the leg during IMN improves clinical and fluoroscopic evaluation of the distal tibia, leading to low rates of malalignment. 14,33 Various semi-extended approaches are covered in detail in the proximal tibia section above.…”
Section: Pearl 5: Semi-extended Positioningmentioning
confidence: 99%
“…In contrast, the semi-extended IMN technique has shown much more favorable results. 14,29,33 A recent retrospective review by Avilucea, et al demonstrated a 3.8% rate of malalignment in distal tibia fractures treated with a suprapatellar approach compared to a 26.1% rate of malalignment in those treated with an infrapatellar approach. 33 intraoperative malalignment.…”
Section: Distal Tibia Literaturementioning
confidence: 99%
See 2 more Smart Citations